Nitrogen and potassium fertilization in corn in an Alfisol of Guanacaste, Costa Rica - Garbanzo-León, Gabriel (2021)
Introduction. In Guanacaste, Costa Rica, corn (Zea mays) has been a cultural crop for consumption since pre-Colombian times. Many farmers have set aside areas for its planting in association with other crops. However, the varieties used require fertilization and plant nutrition studies to improve ear quality and postharvest life. Objective. To evaluate the effect of increasing doses of nitrogen and potassium in the J-Saenz maize variety, in combination with three sowing densities. Materials and methods. The study was conducted at the Santa Cruz Experimental Farm, Universidad de Costa Rica, in 2018. Three doses of N (100, 200, 300 kg ha-1 with a base of 160 kg ha-1 of K2O) and K2O (100, 160 and 200 kg ha-1 with a base of 300 kg N ha-1) were evaluated with three sowing densities (50 000, 57 143, and 66 667 plants ha-1) with the J-Sáenz variety. The crop yield, the percentage of exposed ear, and the accumulation of nutrients in the phenological R5 stage were evaluated. The data were subjected to analysis of variance with a factorial structure and generalized linear models with DGS tests of means separation. Results. There was a significant increase in grain production by increasing the sowing density from 50 000 to 66 667 plants ha-1. The highest efficiency in the N and K use was achieved with the application of 100 kg ha-1 of each element at a density of 57 000 plants ha-1. The exposed ear variable was not related to nutrient doses. Corn increased absorption with increasing doses of N but not K. Conclusion. The planting density of 57 143 plants ha-1 showed the best yield at doses of 100 kg of N ha-1 and 100 kg of K2O ha-1.